Gray Matter Vulnerabilities Predict Longitudinal Development of Apathy in Huntington's Disease. Issue 9 (17th May 2021) - De Paepe, Audrey E.; Ara, Alberto; Garcia‐Gorro, Clara; Martinez‐Horta, Saül; Perez‐Perez, Jesus; Kulisevsky, Jaime; Rodriguez‐Dechicha, Nadia; Vaquer, Irene; Subira, Susana; Calopa, Matilde; Muñoz, Esteban; Santacruz, Pilar; et al.
Abstract: Background: Apathy, a common neuropsychiatric disturbance in Huntington's disease (HD), is subserved by a complex neurobiological network. However, no study has yet employed a whole‐brain approach to examine underlying regional vulnerabilities that may precipitate apathy changes over time. Objectives: To identify whole‐brain gray matter volume (GMV) vulnerabilities that may predict longitudinal apathy development in HD. Methods: Forty‐five HD individuals (31 female) were scanned and evaluated for apathy and other neuropsychiatric features using the short‐Problem Behavior Assessment for a maximum total of six longitudinal visits (including baseline). In order to identify regions where changes in GMV may describe changes in apathy, we performed longitudinal voxel‐based morphometry (VBM) on those 33 participants with a magnetic resonance imaging (MRI) scan on their second visit at 18 ± 6 months follow‐up (78 MRI datasets). We next employed a generalized linear mixed‐effects model (N = 45) to elucidate whether initial and specific GMV may predict apathy development over time. Results: Utilizing longitudinal VBM, we revealed a relationship between increases in apathy and specific GMV atrophy in the right middle cingulate cortex (MCC). Furthermore, vulnerability in the right MCC volume at baseline successfully predicted the severity and progression of apathy over time. Conclusions: This study highlights that individual differences in apathy in HD may be explained by variability in atrophy and initial vulnerabilities in the right MCC, a region implicated in action‐initiation. These findings thus serve to facilitate the prediction of an apathetic profile, permitting targeted, time‐sensitive interventions in neurodegenerative disease with potential implications in otherwise healthy populations. © 2021 International Parkinson and Movement Disorder Society